2016
DOI: 10.24953/turkjped.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease shock syndrome: a rare and severe complication of Kawasaki disease

Abstract: Kawasaki disease is an acute systemic vasculitis that occurs most commonly in young children. It affects medium-sized muscular arteries and the coronary arteries are the predominant site of involvement. Morbidity and mortality is generally due to coronary artery aneurysms that develop during the chronic phase. Although it is well known that Kawasaki disease can cause myocarditis, tachycardia and heart failure during acute stage, Kawasaki disease shock syndrome has been recently described. It is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Heparin anticoagulation [10 U/(kg.d) of heparin concurrently two h before the start of methylprednisolone] for 24 h is recommended, or low-molecular heparin anticoagulation with coagulation, echocardiography, and blood pressure monitoring (2A). [47][48][49][50] First-line treatment of KD combined with MAS Recommendation: Methylprednisolone 10-30 mg/ (kg.d) for 3 d, with each IV infusion for 2-3 h. Sequential prednisone orally [1-2 mg/(kg.d)] until complete control and remission of MAS with gradual dose reduction and discontinuation (2A) [51][52][53] GC is not recommended as routine first-line therapy for KD. GC alone is unsafe and contraindicated as a first-line treatment for KD, as studies have shown that GC alone used as an initial treatment for KD can significantly increase coronary artery damage.…”
Section: Bmentioning
confidence: 99%
“…Heparin anticoagulation [10 U/(kg.d) of heparin concurrently two h before the start of methylprednisolone] for 24 h is recommended, or low-molecular heparin anticoagulation with coagulation, echocardiography, and blood pressure monitoring (2A). [47][48][49][50] First-line treatment of KD combined with MAS Recommendation: Methylprednisolone 10-30 mg/ (kg.d) for 3 d, with each IV infusion for 2-3 h. Sequential prednisone orally [1-2 mg/(kg.d)] until complete control and remission of MAS with gradual dose reduction and discontinuation (2A) [51][52][53] GC is not recommended as routine first-line therapy for KD. GC alone is unsafe and contraindicated as a first-line treatment for KD, as studies have shown that GC alone used as an initial treatment for KD can significantly increase coronary artery damage.…”
Section: Bmentioning
confidence: 99%
“…Some investigators, including Todd et al [58], who named TSS, have described cases of KS superimposed on TSS [59]. Additionally, there have been multiple reports of a KS-shock syndrome [60,61].…”
Section: Laboratory Findings In Ksmentioning
confidence: 99%
“…Myocarditis is nearly universal in acute phase of KD and, at times, it can be severe and symptomatic[ 58 , 59 ]. These patients are usually admitted in intensive care units with cardiovascular collapse and may be mistakenly treated for bacterial sepsis and septic shock[ 13 , 60 , 61 ]. As a result, the diagnosis of KD gets delayed and this can have serious consequences.…”
Section: Controversies In Diagnosis Of Kdmentioning
confidence: 99%